Manajemen Kesiswaan pada Sekolah Dasar Negeri 02 Banyuasin II - Rahma Yanti, Devi; Ade Akhmad Saputra (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
The purpose of this study was to determine and analyze student management at SD Negeri 02 Banyuasin II, which is located in Teluk Payo Village. A descriptive qualitative approach was used to collect data through observation, documentation, and interviews. One of the informants in this study was the principal of SD Negeri 02 Banyuasin II, who is also the manager of the educational institution. The data analysis techniques used included data reduction, data presentation, and conclusion drawing. The results showed that this school has carried out student management well, especially in terms of student management that has been used effectively to support educational activities. The management includes organizing new student admissions, orientation, attendance, extracurricular activities, and student evaluation. However, some obstacles were still found, such as the lack of fulfillment of students' administrative documents, especially birth certificates, as well as parental involvement that still needs to be improved. This study recommends the need for further socialisation to parents regarding the importance of administrative documents and improving communication between schools and parents to support students' educational success.